Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Interpretable causal machine learning elucidates performance regulation via atomic Fe‑S synergistic pathways in Sulfidated zero‑valent Iron - Zimin Yan; Rupeng Wang; Zhiling Li; Tianyi Huang; Yunxia Zu; Xiaoxi Zeng; Di Cao; Bin Wu; Jun Huang; Shih-Hsin Ho; Aijie Wang (Water Research, 2026)

Hexamermis jengi n. sp. (Nematoda: Mermithidae) parasitizing grasshoppers and the invasive fall armyworm in Taiwan and Thailand - Ping-Chieh Lee; Ace Kevin S. Amarga; Wen-Hua Chen; Li-Hsin Wu; Chuan-Kai Ho; Chun-I Chiu; Ming-Chung Chiu (Journal of Invertebrate Pathology, 2026)

Source-specific VOCs and atmospheric oxidation capacity drive the formation of secondary aerosols and visibility impairment in East Asia suburban environments - Tse-Lun Chen; Kuan-Chieh Lee; Jun-Fa Yeh; Jian-Xian Wu; Li-Hao Young; Neng-Huei Lin; Si-Chee Tsay; Wen-Yinn Lin; Chia-Hsin Lin; Ta-Chih Hsiao (Journal of Hazardous Materials, 2026)

Short-duration electrical pulse stimulation induces myokines and mitochondrial adaptations in C2C12 myotubes - Shih-Hua Fang; Ming-Ru Chiang; Chia-Yang Li; Pei-Ying Li; Zong-Jia Wu; Hsin-Hua Li (Journal of Muscle Research and Cell Motility, 2026)

Dehydroxylation and amorphization of wet serpentinite gouges during experimental seismic slip and implications for coseismic fluid drainage - Li-Wei Kuo; Wei-Hsin Wu; Matthew S. Tarling; Steven A.F. Smith; Thi Trinh Nguyen; Wen-Jie Wu; Jialiang Si (Journal of Structural Geology, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Iron-reduction driven extracellular electron transfer widely promotes microbial reductive dechlorination metabolism - Yunxia Zu; Zhiling Li; Zimeng Zhang; Xueqi Chen; Bin Wu; Shih-Hsin Ho; Aijie Wang (Water Research, 2025)

Effects of pyrolysis temperature on the biochar-derived horse manure: Physicochemical characteristics and catalytic activation of peroxymonosulfate activation toward sulfamethoxazole degradation in aqueous solution - Li-Min Chiang; Thanh-Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong; Chung-Hsin Wu (Journal of Water Process Engineering, 2025)

Ilimaquinone induces apoptosis in gastric cancer cells by inhibiting the signal transducer and activator of the transcription 3 pathway - Jui-Hsin Su; Li-Yuan Bai; Chia-Yung Wu; Chia-Hsien Feng; Jing-Ru Weng (Chemico-Biological Interactions, 2025)

Green modification of forward osmosis membrane using lignocellulosic biomass for water and valuable resource recovery from seawater brine - Yi Li Lin; Nai Yun Zheng; Shih Hsin Pan; Yun Shan Wu; Chao Chin Chang (Journal of Water Process Engineering, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Eplerenone improves hyperglycemia and sympathetic excitation in chronic renocardiac syndrome in rats - Chieh-Jen Wu; Yu-He Li; Fu-Zong Wu; Hsin-Hung Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Utilizing Numerical Models and GIS to Enhance Information Management for Oil Spill Emergency Response and Resource Allocation in the Taiwan Waters - Chi-Min Chiu; Laurence Zsu-Hsin Chuang; Wei-Liang Chuang; Li-Chung Wu; Ching-Jer Huang; Yinglong Joseph Zhang (Journal of Marine Science and Engineering, 2023)
This study aims to establish a comprehensive workflow for developing emergency response plans for both actual and scenario oil spill incidents in the Taiwan waters while addressing the resource allocation for oil spill containment as well. This workflow comprises two vital components. The first component involves the integration of numerical tools and observational data, which includes the incorporation of wind data from sources such as the National Centers for Environmental Prediction (NCEP) or meteorological stations. Additionally, it incorporates ocean current data simulated by the semi-implicit cross-scale hydroscience integrated system model (SCHISM) into the general NOAA operational modeling environment (GNOME) model, which is a new approach for this purpose. In order to assess the efficacy of this component, two distinct case studies were conducted. The first case study focused on an incident in a northern coastal area of Taiwan under open sea conditions, whereas the second case study examined an incident within a major commercial harbor in central Taiwan. The second component of this workflow involves creating oil risk maps by integrating the results from the first component with specific geographical factors into Google Earth. These oil risk maps serve multiple purposes. They offer real-time information to emergency response commanders regarding oil spill hazard prediction, and they also enable the effective development of emergency response strategies and disposal plans for potential oil spill incidents. This is achieved by generating risk maps for various scenarios using the approach outlined in the first component. Additionally, these maps assist in the assessment and planning of resource allocation for oil containment.

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Entomopathogenic fungi-mediated biological control of the red palm weevil Rhynchophorus ferrugineus - Tzu-Hao Yang; Li-Hsin Wu; Chung-Ta Liao; Dongwei Li; Tae Young Shin; Jae Su Kim; Yu-Shin Nai (Journal of Asia-Pacific Entomology, 2023)

Algal-fungal interactions and biomass production in wastewater treatment: Current status and future perspectives - Wenbo Wu; Shengnan Li; Peng Xie; Xue Li; Haixing Chang; Shih-Hsin Ho (Algal Research, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

Bragg-region recognition of high-frequency radar spectra based on deep learning and image fusion processing - Laurence Zsu-Hsin Chuang; Yu-Ru Chen; Yu-Jen Chung; Li-Chung Wu; Tsung-Mo Tien (International Journal of Remote Sensing, 2022)

Blocking Hepatoma-Derived Growth Factor Attenuates Vasospasm and Neuron Cell Apoptosis in Rats Subjected to Subarachnoid Hemorrhage - Chia-Li Chung; Chieh-Hsin Wu; Yu-Hua Huang; Shu-Chuan Wu; Chee-Yin Chai; Hung-Pei Tsai; Aij-Lie Kwan (Translational Stroke Research, 2022)
Subarachnoid hemorrhage (SAH) is an important subcategory of stroke due to its unacceptably high mortality rate as well as the severe complications it causes, such as cerebral vasospasm, neurological deficits, and cardiopulmonary abnormality. Hepatoma-derived growth factor (HDGF) is a growth factor related to normal development and is involved in liver development and regeneration. This study explored the relationship between SAH and HDGF. Sixty rats were divided into five groups (n = 12/group): (A) control group; (B) rHDGF ab only group [normal animals treated with 50 µM recombinant HDGF antibodies (rHDGF ab)]; (C) SAH group; (D) SAH + pre-rHDGF ab group (SAH animals pre-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h before SAH); and (E) SAH + post-rHDGF ab group (SAH animals post-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h after SAH). At 48 h after SAH, serum and cerebrospinal fluid (CSF) samples were collected to measure the levels of pro-inflammatory factors by ELISA, and rat cortex tissues were used to measure protein levels by western blot analysis. Immunofluorescence staining for Iba-1, GFAP, TUNEL, and NeuN was detected proliferation of microglia and astrocyte and apoptosis of neuron cells. Neurological outcome was assessed by ambulation and placing/stepping reflex responses. Morphology assay showed that pre-treatment and post-treatment with rHDGF ab attenuated vasospasm after SAH. SAH up-regulated the levels of TNF-α, IL-1β, and IL-6 in both the CSF and serum samples, and both pre- and post-treatment with rHDGF ab inhibited the up-regulation of these pro-inflammatory factors, except for the serum IL-6 levels. Western blot analysis demonstrated that SAH up-regulated pro-BDNF and NFκB protein levels, and both pre- and post-treatment with rHDGF ab significantly reduced the up-regulation. The result from immunofluorescence staining showed that SAH induced proliferation of microglia and astrocyte and apoptosis of neuron cells. Both pre- and post-treatment with rHDGF ab significantly attenuated proliferation of microglia and astrocyte and inhibited apoptosis of neuron cells. Furthermore, treatment with rHDGF ab significantly improved neurological outcome. Blocking HDGF attenuates neuron cell apoptosis and vasospasm through inhibiting inflammation in brain tissue at early phase after SAH.

Unraveling microbiomes associated with decomposition of needles of two Pinus species with contrasting fire-adaptive strategies - Hsin-Ni Liu; Tsai-Wen Hsu; Yi-Hung Wu; Chao-Li Huang (Biology and Fertility of Soils, 2021)

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Anti-oxidative Responses on Hepatic Tissue of Zebrafish (Danio rerio) in a Short Duration of Sub-lethal Concentrations of Cadmium Exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu; Ching Hsein Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

Basinwide disaster loss assessments under extreme climate scenarios: a case study of the Kaoping River basin - Hsin-Chi Li; Tingyeh Wu; Hsiao-Ping Wei; Hung-Ju Shih; Yi-Chiung Chao (Natural Hazards, 2017)

Role of Rhizophagus irregularis in alleviating cadmium toxicity via improving the growth, micro- and macroelements uptake in Phragmites australis - Li Wang; Xiaochen Huang; Fang Ma; Shih-Hsin Ho; Jieting Wu; Shishu Zhu (Environmental Science and Pollution Research, 2017)

Anti-oxidative functions of mt2 and smtB mRNA expression in the gills and brain of zebrafish (Danio rerio) upon cadmium exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu (Fish Physiology and Biochemistry, 2016)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

SMN is required for the maintenance of embryonic stem cells and neuronal differentiation in mice - Wei-Fang Chang; Jie Xu; Chia-Chun Chang; Shang-Hsun Yang; Hsin-Yang Li; Hsiu Mei Hsieh-Li; Mong-Hsun Tsai; Shinn-Chih Wu; Winston T. K. Cheng; Ji-Long Liu; Li-Ying Sung (Brain Structure and Function, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Ocean remotely sensed image analysis using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Quantification of non-homogeneity from ocean remote-sensing images using two-dimensional continuous wavelet transforms - Li-Chung Wu; Laurence Zsu-Hsin Chuang; Dong-Jiing Doong; Chia Chuen Kao (International Journal of Remote Sensing, 2011)

Anticancer efficacy of 5F in NNK-induced lung cancer development of A/J mice and human lung cancer cells - Ming-Yue Li; Jackie Leung; Angel W. Y. Kong; Nian Ci Liang; Kefeng Wu; Michael K. Y. Hsin; Yi Feng Deng; Xianling Gong; Yingnian Lv; Tony S. K. Mok; Malcolm J. Underwood; George G. Chen (Journal of Molecular Medicine, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Nonlinear influences on ocean waves observed by X-band radar - Li-Chung Wu; Dong-Jiing Doong; Beng-Chun Lee; Laurence Zsu-Hsin Chuang; Chia Chuen Kao (Marine Geophysical Research, 2008)